SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Public perceptions of per- and polyfluoroalkyl substances (PFAS): Psycho-demographic characteristics differentiating PFAS knowledge and concern - Joya A. Kemper; Emma Sharp; Shan Yi; Erin M. Leitao; Lokesh P. Padhye; Melanie Kah; Jack L.-Y. Chen; Kapish Gobindlal (Journal of Cleaner Production, 2024)

Top ten priorities for global saltmarsh restoration, conservation and ecosystem service research - Julien Pétillon; Emma McKinley; Meghan Alexander; Janine B. Adams; Christine Angelini; Thorsten Balke; John N. Griffin; Tjeerd Bouma; Sally Hacker; Qiang He; Marc J.S. Hensel; Carles Ibáñez; et al. (Science of The Total Environment, 2023)

Feasibility and acceptability of an acceptance-based guided self-help programme for weight loss maintenance - Julia Mueller; Rebecca A. Jones; Rebecca Richards; Jennifer Woolston; Fiona Whittle; Andrew J. Hill; Carly A. Hughes; Robbie Duschinsky; Stephen J. Sharp; Clare Boothby; Jennifer Bostock; Penny Breeze; et al. (Appetite, 2023)

Use of multiple endpoints to assess the impact of captivity on gut flora diversity in Long Island Sound Fundulus heteroclitus - Joseph P. Battaglia; Christian M. Kearney; Kirsten Guerette; Jordan Corbishley; Emily Sanchez; Brennah Kent; Hanna Storie; Emma Sharp; Shane Martin; Matthew Saberito; Jonathan D. Blake; Richard S. Feinn; et al. (Environmental Biology of Fishes, 2022)

Foundation species patch configuration mediates salt marsh biodiversity, stability and multifunctionality - Sinéad M. Crotty; Sean J. Sharp; Ada C. Bersoza; Kimberly D. Prince; Katheryne Cronk; Emma E. Johnson; Christine Angelini (Ecology Letters, 2018)
Foundation species enhance biodiversity and multifunctionality across many systems; however, whether foundation species patch configuration mediates their ecological effects is unknown. In a 6‐month field experiment, we test which attributes of foundation species patch configuration – i.e. patch size, total patch area, perimeter, area‐perimeter ratio, or connectivity – control biodiversity, stability and multifunctionality by adding a standardised density of mussel foundation species in patches of 1, 5, 10, 30, 60, 90 or 180 individuals to a southeastern US salt marsh. Over 67% of response variables increased with clustering of mussels, responses that were driven by increases in area–perimeter ratio (33%), decreases in perimeter (29%), or increases in patch size (5%), suggesting sensitivity to external stressors and/or dependence on foundation species‐derived niche availability and segregation. Thus, mussel configuration – by controlling the relative distribution of multidimensional patch interior and edge niche space – critically modulates this foundation species’ effects on ecosystem structure, stability and function.